Electrical and optical characterisation of silicon nanocrystals embedded in SiC - Schnabel, M; Löper, P; Canino, M; Dyakov, SA; Allegrezza, M; Bellettato, M; López-Vidrier, J; Hernández, S; Summonte, C; Garrido, B; Wilshaw, P; Janz, S (Trans Tech Publications Ltd, 2014)
Silicon nanocrystals (Si NCs) are a promising candidate for the top cell of an all-Si tandem solar cell with a band gap from 1.3-1.7 eV, tuneable by adjusting NC size. They are readily produced within a Si-based dielectric matrix by precipitation from the Si excess in multilayers of alternating stoichiometric and silicon-rich layers. Here we examined the luminescence and transport of Si NCs embedded in SiC. We observed luminescence that redshifts from 2.0 to 1.5 eV with increasing nominal NC size. Upon further investigation, we found that this redshift is to a large extent due to Fabry-Pérot interference. Correction for this effect allows an analysis of the spectrum emitted from within the sample. We also produced p-i-n solar cells and found that the observed I-V curves under illumination could be well-fitted by typical thin-film solar cell models including finite series and parallel resistances, and a voltage-dependent current collection function. A minority carrier mobility-lifetime product on the order of 10-10 cm2/V was deduced, and a maximum open-circuit voltage of 370 mV achieved. © (2014) Trans Tech Publications, Switzerland.